The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21103728
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxidative Stress Modulates Alveolar Bone Loss in Chronically Stressed Rats

Abstract: We aimed to investigate the effects of chronic stress (CS) on experimental periodontitis (EP) in rats. For this, 28 Wistar rats were divided into four groups: control, ligature-induced experimental periodontitis (EP), chronic stress (CS; by physical restraint model) and CS+EP (association of chronic stress and ligature-induced periodontitis). The experimental period lasted 30 days, including exposure to CS every day and ligature was performed on the 15th experimental day. After 30 days, the animals were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
4
11
0
Order By: Relevance
“…Accompanying the results of increased CORT and ACTH contents as well as decreased sucrose preference, we confirmed that the CUMS protocol in this study induced a depression-like state in the PS and EP+PS animals. In addition, because it causes plaque retention, the method used in this study of tying a ligature around the teeth is widely used to establish periodontal disease in animals [ 8 , 11 , 12 , 14 ]. Although we did not find any changes in alveolar bone loss, attachment loss, or cytokine protein expression in the gingiva of stressed rats, we confirmed that multiple stressors worsened these parameters in rats with silk ligature-induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accompanying the results of increased CORT and ACTH contents as well as decreased sucrose preference, we confirmed that the CUMS protocol in this study induced a depression-like state in the PS and EP+PS animals. In addition, because it causes plaque retention, the method used in this study of tying a ligature around the teeth is widely used to establish periodontal disease in animals [ 8 , 11 , 12 , 14 ]. Although we did not find any changes in alveolar bone loss, attachment loss, or cytokine protein expression in the gingiva of stressed rats, we confirmed that multiple stressors worsened these parameters in rats with silk ligature-induced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to suppose that hypoxia occurs in the periodontium [ 36 ] when rats undergo long-term stress. Lopes Castro et al [ 12 ] have reported oxidative imbalance in a blood sample and consider that the disequilibrium of oxidation and antioxidation could potentialize or generate alveolar bone lesions in chronically stressed rats. In the current study, we first observed that the local anomalous redox trend was worse in the inflamed gingiva following psychological stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the emerging evidence, in their review article, Aquino-Martinez et al proposed a new scientific model that senescent cells, which receive oxidative stress and subsequent DNA damage, may aggravate the innate immune reaction against pathogens [ 12 ]. Lopes et al indicated that chronic stress-induced blood oxidative stress exacerbates periodontal bone resorption using the rat physical restraint model [ 13 ].…”
mentioning
confidence: 99%